Analysis of lower limb movement to determine the effect of manipulating the appearance of stairs to improve safety: a linked series of laboratory-based, repeated measures studies - David B Elliott; Richard J Foster; David Whitaker; Andrew J Scally; John G Buckley (NIHR Journals Library, 2015)
Background: Falls on stairs are a common and dangerous problem for older people. This series of studies evaluated whether or not selected changes to the appearance of stairs could make them safer for older people to negotiate. Objectives: To determine the effect of (1) a step edge highlighter and its position and (2) an optimised horizontal-vertical (H-V) visual illusion placed on a step riser on gait safety during stair descent and ascent. Design: A series of studies using a repeated measures, laboratory-based design, investigating gait control and safety in independently mobile older people. Setting: The University of Bradford Vision and Mobility Laboratory. Participants: Fit and healthy older people aged 60 years of age or more, independently mobile, reasonably active and with normal healthy eyes and corrected vision. Interventions: A step edge highlighter in a variety of offsets from the stair edge and an optimised H-V visual illusion placed on the stair riser. The H-V illusion was provided on a staircase by horizontal step edge highlighters on the tread edges and vertical stripes on the step risers. Main outcome measures: Gait parameters that are important for safe stepping in ascent and descent, particularly toe clearance during stair ascent and heel clearance during stair descent. Results: The step edge highlighter increased the precision of heel clearance during stepping and its positioning relative to the tread edge determined the extent of heel clearance over the tread edge. Positioning the highlighter away from the tread edge, as is not uncommonly provided by friction strips, decreased heel clearance significantly and led to greater heel scuffs. Although psychophysics experiments suggested that higher spatial frequencies of the H-V illusion might provide greater toe clearance on stair ascent, gait trials showed similar increased toe clearances for all spatial frequencies. When a 12 cycle per step spatial frequency H-V illusion was used, toe clearance increases of approximately 1 cm (17.5%) occurred without any accompanying changes in other important gait parameters or stability measures. Conclusions: High-contrast tread edge highlighters present on steps and stairs and positioned flush with the edge of the tread or as near to this as possible should improve stair descent safety in older people. A H-V illusion positioned on the riser of a raised surface/walkway (e.g. kerbs) and/or the top and/or bottom of a stairway is likely to increase foot clearance over the associated step/stair edge, and appears not to lead to any decrement in postural stability. Thus, their use is likely to reduce trip risk and hence improve stair ascent safety. The effect of the step and stair modifications should be assessed in older people with visual impairment. The only other remaining assessment that could be made would be to assess fall prevalence on steps and stairs, perhaps in public buildings, with and without these modifications. Funding: The National Institute for Health Research Public Health Research programme.